IMPROVING THE QUALITY OF COCONUT-BASED CRAFT PRODUCTS AND SOUVENIR CRAFTS ZONATION AS A SPECIAL TOURISM OF NORTH SULAWESI - Agustinus Walansendow, Silvya Mandey, Lisbeth Mananeke, Herman Karamoy (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Industrial center is the coconut base material industrial sectors that can support community economic empowerment in North Sulawesi Province such as furniture manufacturing, coconut oil, coconut flour, copra, cake, and shell charcoal. Also, there is a home industry craft business made of wood and coconut shell but still requires special handling. This research aims to describe the characteristics of souvenirs from the basic materials of wood and coconut shell characterized by North Sulawesi, and the mapping of the craftsmen industry groups so that they are easily monitored to guarantee the quality of their products. This research was descriptive qualitative. This study used primary and secondary data through interviews, field observations and information studies. The results of the study found that coconut-based handicraft products need to be improved and need special treatment because the reality obtained in the field is found; Existing souvenirs do not describe the identity of attractions, the quality of souvenirs is still low, and not yet attractive. expensive souvenir prices / not by its quality. Souvenir size is too large and not packaged and difficult to take home. Souvenirs offered is not only the goods but the but it can be in the form of objects from nature that is environmentally friendly.